2012
DOI: 10.7196/samj.5793
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of short- and long-term case fatality within an incident stroke population in Tanzania

Abstract: Background. This study aimed to identify correlates of case fatality within an incident stroke population in rural Tanzania. Methods. Stroke patients, identified by the Tanzanian Stroke Incidence Project, underwent a full examination and assessment around the time of incident stroke. Records were made of demographic data, blood pressure, pulse rate and rhythm, physical function (Barthel index), neurological status (communication, swallowing, vision, muscle activity, sensation), echocardiogram, chest X-ray and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Thirty two studies assessed overall mortality due to stroke. Twelve studies were from Africa [7][8][17][18][19][20][21][22][23][24][25][26], six from Europe [27][28][29][30][31][32], six from Asia [33][34][35][36][37][38], five from North America [39][40][41][42][43] and two from Latin America [44][45].Seventeen studies reported 30-day mortality rate of stroke whereas twenty two studies measured in-hospital mortality. Detailed explanations on study characteristics are shown in the supplementary table (table 1).…”
Section: Study Characteristics and The Selection Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty two studies assessed overall mortality due to stroke. Twelve studies were from Africa [7][8][17][18][19][20][21][22][23][24][25][26], six from Europe [27][28][29][30][31][32], six from Asia [33][34][35][36][37][38], five from North America [39][40][41][42][43] and two from Latin America [44][45].Seventeen studies reported 30-day mortality rate of stroke whereas twenty two studies measured in-hospital mortality. Detailed explanations on study characteristics are shown in the supplementary table (table 1).…”
Section: Study Characteristics and The Selection Processmentioning
confidence: 99%
“…While the annual incidence of stroke declined in HICs, it increased in the LMICs by more than 100% to surpass that of the HIC. 6 The burden in LMICs has also been higher in terms of prevalence, deaths, and DALYs lost [3,6].Previous studies reported different rate of mortality of stroke ranged from (11.97%-60%) [7][8]which indicate the requirement of comprehensive data on stroke mortality globally.…”
Section: Introductionmentioning
confidence: 99%
“…The number of survivors at 7 years was too small to allow meaningful analysis of a wider range of variables as predictors of case‐fatality. However, correlates of three‐year case‐fatality in this cohort have been described previously 6.…”
Section: Discussionmentioning
confidence: 82%
“…Post-stroke outcomes vary widely between, and within, world regions depending on a range of factors including demographic profile, stroke type and severity and immediate and long-term poststroke care (3)(4)(5)(6). However, long-term post-stroke outcomes in SSA are poorly described, with most studies being hospital-based.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation